A method for preparing an aqueous zinc ion battery with symmetrical three-dimensional positive and negative electrodes
By preparing a three-dimensional carbon fiber network current collector from the eggshell membrane, the MnO2 nanowire positive electrode and zinc negative electrode were grown in situ, and a zinc ion battery with a symmetric three-dimensional structure was constructed, which solved the problem of inconsistent energy density and electrochemical reaction rate of the existing battery, and achieved higher mass energy density and more stable cycling performance.
Patent Information
- Application Number
- CN202210653751.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-09
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-06-09
AI Technical Summary
The energy density of existing aqueous zinc ion batteries is not ideal, and the contact area between the traditional two-dimensional electrode structure and the electrolyte is limited, resulting in inconsistent electrochemical reaction rates and affecting the cycling performance of the battery.
The eggshell membrane was separated from the eggshell by acid solution, and a three-dimensional carbon fiber network current collector was prepared by high-temperature heat treatment, and the MnO2 nanowire positive electrode and zinc negative electrode were grown in situ to build a zinc ion battery with a symmetric three-dimensional structure to ensure the consistent electrochemical reaction rate of the positive and negative electrodes.
By building a zinc ion battery with a symmetric three-dimensional structure, it provides more electrochemical reaction sites, improves the mass energy density of the battery, and has a smoother circulation performance, making it suitable for wearable devices with high safety and energy density requirements.
Smart Images

Figure CN115020828B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal ion batteries, and in particular relates to a method for preparing an aqueous zinc ion battery with positive and negative electrodes having a symmetrical three-dimensional structure. Background Art
[0002] At present, lithium-ion batteries have been widely used in consumer electronics, electric vehicles, and large-scale energy storage power stations for renewable energy. However, the high price of lithium and the uneven distribution of resources have seriously limited the sustainable application of lithium-ion batteries in the future. In addition, wearable devices will be an emerging high-tech market with huge potential. Implanting power sources, circuits, and functional electronic components (such as sensors, communication equipment, and smart chips) into clothes to make smart clothes is considered to be the most important development direction for wearable devices in the future. However, lithium-ion batteries use toxic and flammable organic electrolytes, which also limits their safe application in wearable devices.
[0003] Aqueous zinc-ion secondary batteries have the advantages of low cost, high safety, and environmental friendliness. They are a new type of secondary battery suitable for wearable device applications, but the energy density of aqueous zinc-ion batteries is still not ideal. The traditional electrode preparation process of aqueous zinc-ion batteries usually involves preparing electrode materials, conductive agents, and adhesives into slurry and then coating them on a two-dimensional structured current collector (such as stainless steel foil, titanium foil, stainless steel mesh, and carbon cloth). The improvement of the battery's specific energy density is limited by the contact area between the planar electrode and the electrolyte. In addition, the use of conductive agents, adhesives, and metal foils inevitably reduces the energy density of the battery. Therefore, further designing and optimizing the electrode structure has always been a research hotspot for aqueous zinc-ion batteries, and the three-dimensional structure can provide more active sites for electrochemical reactions, thereby greatly improving the energy density of the battery. Therefore, the construction of three-dimensional structure electrodes has attracted the interest of many researchers.
[0004] At present, the current collector of the three-dimensional electrode is mainly made by coating or electrodepositing the electrode material on a three-dimensional porous foam metal skeleton (such as foam stainless steel, foam nickel, foam titanium, etc.), but the high mass density of the metal current collector will reduce the specific energy density of the battery. At present, in terms of the utilization of three-dimensional electrodes, the main method is to prepare the positive or negative electrode of the three-dimensional structure separately, while the other pair of electrodes is still a planar electrode, thereby forming a full battery with an asymmetric structure. For example, Chinese invention patent CN113046795A discloses a negative electrode galvanized in a three-dimensional titanium structure, and the cycle performance curve of the zinc ion battery prepared by it and the MnO2 positive electrode is characterized by a low discharge capacity at the beginning, and the capacity quickly rises to an extreme value within dozens of cycles as the cycle proceeds, and then the phenomenon of attenuation occurs as the cycle proceeds. Because the positive electrode of the three-dimensional structure exposes more surface area in contact with the electrolyte relative to the planar electrode, resulting in asymmetric positive and negative electrode reaction rates, the slower electrochemical reaction rate of the planar electrode makes the three-dimensional structure electrode fail to achieve the expected performance. Therefore, zinc-ion batteries with symmetrical three-dimensional positive and negative electrodes will be suitable for wearable devices with high requirements for safety and energy density. Summary of the invention
[0005] In order to overcome the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing an aqueous zinc ion battery with positive and negative electrodes having a symmetrical three-dimensional structure, wherein the electrochemical reaction rates of the positive and negative electrodes of the prepared aqueous zinc ion battery are consistent, more electrochemical reaction sites can be provided, and the battery has a higher mass energy density.
[0006] To achieve the above object, the present invention is implemented by the following technical solutions:
[0007] The present invention provides a method for preparing an aqueous zinc ion battery having positive and negative electrodes with symmetrical three-dimensional structures, the method comprising the following steps:
[0008] S1, separating the eggshell membrane from the eggshell with an acid solution, drying it, and then heat-treating it under high temperature atmosphere to obtain a three-dimensional carbon fiber network current collector;
[0009] S2, firstly prepare a reaction solution with sodium dodecylbenzene sulfonate, potassium permanganate and water, then place the three-dimensional carbon fiber network current collector of step S1 in the reaction solution, in situ grow MnO2 nanowires on the three-dimensional carbon fiber network current collector after hydrothermal reaction, and then obtain well-crystallized three-dimensional MnO2 nanowires after calcination;
[0010] S3, using the three-dimensional carbon fiber network current collector of step S1 as a working electrode, and metal as a counter electrode and a reference electrode, and depositing for a period of time in a constant potential deposition manner to obtain a zinc-plated three-dimensional carbon fiber network current collector;
[0011] S4, using the three-dimensional MnO2 nanowires of step S2 as the positive electrode and the galvanized three-dimensional carbon fiber network current collector of step S3 as the negative electrode, forming a sandwich structure with the diaphragm and injecting a zinc salt-containing electrolyte, and packaging according to shell-type or soft-pack battery technology to obtain a zinc ion battery with symmetrical three-dimensional positive and negative electrodes.
[0012] Preferably, the eggshell is an eggshell of poultry (such as chicken, duck, goose).
[0013] Poultry eggshell membrane is an easily available low-cost biomass. After carbonization, a low-mass-density three-dimensional carbon fiber network current collector can be obtained. In-situ growth of electrode materials on it to prepare three-dimensional structured electrodes can also avoid the use of metal current collectors, binders and conductive additives, thereby effectively improving the mass energy density of the battery. The preparation of zinc-ion batteries with symmetrical three-dimensional positive and negative electrodes will be suitable for wearable devices with high requirements for safety and energy density.
[0014] The present invention prepares eggshell membrane into a three-dimensional carbon fiber network current collector through high temperature heat treatment, and then in-situ grows a three-dimensional MnO2 nanowire positive electrode and a three-dimensional zinc negative electrode for a zinc ion battery using the obtained three-dimensional carbon fiber network current collector, and thereby constructs a high specific energy zinc ion battery with symmetrical three-dimensional positive and negative electrodes. The preparation of the three-dimensional MnO2 positive electrode is to in-situ grow MnO2 nanowires on the three-dimensional carbon fiber network current collector by a hydrothermal method. In addition to increasing the active sites of the three-dimensional structure, the MnO2 nanowires radially shorten the diffusion path of lithium ions, and have a continuous electron transmission channel in the axial direction, which can achieve a rapid electrochemical reaction. The preparation of the three-dimensional zinc negative electrode is to electroplate a zinc film on the three-dimensional carbon fiber network current collector by an electroplating process, and the thickness of the zinc film can be easily regulated by changing the electroplating time and potential, so that the electrochemical reaction rates of the positive and negative electrodes of the symmetrical three-dimensional positive and negative zinc ion battery are consistent.
[0015] The core of the present invention is that the electrochemical reaction rates of the positive and negative electrodes of the symmetrical three-dimensional structure are consistent, which can provide more electrochemical reaction sites compared to traditional planar structure electrodes, and does not use metal current collectors, binders and conductive agents, thereby improving the mass energy density of the battery.
[0016] Preferably, the acid solution in step S1 comprises 20% acetic acid solution (volume concentration).
[0017] Preferably, the heat treatment in step S1 is performed at a temperature of 1200 to 1400° C. for 6 to 10 hours, and the protective atmosphere used is argon or nitrogen.
[0018] Preferably, the mass volume ratio of sodium dodecylbenzene sulfonate, potassium permanganate and water in step S2 is 0.05-2 g: 0.01-0.1 g: 10-30 mL.
[0019] Preferably, the temperature of the hydrothermal reaction in step S2 is 100 to 230° C., and the time is 5 to 15 hours.
[0020] Preferably, the calcination temperature in step S2 is 250-350° C. and the calcination time is 5-15 hours.
[0021] Preferably, step S3 is to use zinc metal as the counter electrode and the reference electrode, and use a solution containing 0.5-2M zinc salt as the electrolyte.
[0022] Preferably, the potential of the constant potential deposition in step S3 is -1.0 to -0.5 V, and the time is 5 to 30 minutes.
[0023] Preferably, the hydrothermal reaction in step S2 is carried out in a closed high-temperature and high-pressure reactor, wherein the high-temperature and high-pressure reactor has a metal shell, and a heat-resistant and corrosion-resistant polytetrafluoroethylene lining is provided in the metal shell.
[0024] Preferably, step S1 is specifically as follows: soaking the eggshell in an acid solution to separate the eggshell from the eggshell membrane and remove residual substances, washing the membrane with ethanol and water several times, sandwiching the membrane between two high-temperature resistant blocks (such as graphite sheets, alumina blocks, etc.) for drying, and then heat-treating under the protection of a high-temperature atmosphere to obtain a three-dimensional carbon fiber network current collector.
[0025] Preferably, the preparation method of the reaction solution in step S2 is: first add sodium dodecylbenzene sulfonate to water, stir to dissolve, then add potassium permanganate, and stir again to prepare a reaction solution. Alternatively, add sodium dodecylbenzene sulfonate and potassium permanganate to water, and stir to prepare a reaction solution.
[0026] The present invention also provides an aqueous zinc ion battery with positive and negative electrodes having symmetrical three-dimensional structures, which is prepared by the above-mentioned preparation method.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The invention discloses a method for preparing an aqueous zinc ion battery with a symmetrical three-dimensional structure of positive and negative electrodes, wherein a three-dimensional structure MnO2 nanowire positive electrode and a three-dimensional structure zinc negative electrode for a zinc ion battery are grown in situ using a three-dimensional carbon fiber network current collector obtained by carbonizing an eggshell membrane, and a high specific energy zinc ion battery with a symmetrical three-dimensional structure of positive and negative electrodes is constructed. The three-dimensional carbon fiber network current collector is composed of three-dimensional interconnected carbon fibers, which can provide a continuous electron transmission channel; and has interconnected and penetrating holes, which can provide a continuous transmission channel for the electrolyte and improve the rate performance of the battery; the electrochemical reaction rate of the positive and negative electrodes of the zinc ion battery with a symmetrical three-dimensional structure of positive and negative electrodes is consistent, and the cycle performance is more stable, and more electrochemical reaction sites can be provided compared to the two-dimensional structure electrode; compared with the traditional structure electrode, no metal current collector, binder and conductive agent are used, and the mass energy density of the battery can be effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The X-ray diffraction pattern of the three-dimensional structure positive electrode of MnO2 nanowires grown in situ on the three-dimensional carbon fiber network prepared in Example 1;
[0030] Figure 2 This is a scanning electron microscope image of a positive electrode with a three-dimensional structure of MnO2 nanowires grown in situ on a three-dimensional carbon fiber network current collector prepared by a hydrothermal method in Example 1;
[0031] Figure 3 The charge and discharge cycle performance curve of the symmetrical three-dimensional structure positive and negative zinc ion battery in Example 1 at a current density of 50 mA / g (the three-dimensional structured zinc negative electrode is obtained by electroplating zinc on a three-dimensional carbon fiber network current collector for 15 minutes);
[0032] Figure 4 The charge and discharge cycle performance curve of the asymmetric electrode structure zinc ion battery assembled with a symmetrical three-dimensional structure MnO2 positive electrode and a planar structure zinc sheet negative electrode at a current density of 50mA / g in Comparative Example 1 (the difference from Example 1 is that the negative electrode directly adopts a zinc sheet). DETAILED DESCRIPTION
[0033] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0034] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0035] Example 1 A method for preparing an aqueous zinc ion battery with a symmetrical three-dimensional positive and negative electrode
[0036] The method for preparing an aqueous zinc ion battery with a symmetrical three-dimensional positive and negative structure in this embodiment comprises the following steps:
[0037] (1) High-temperature preparation of three-dimensional carbon fiber network current collector
[0038] The eggshell membrane was immersed in a mixed solution of 20% acetic acid and 80% deionized water for 24 hours. The eggshell membrane was manually peeled off and washed twice with anhydrous ethanol and deionized water, and then flattened and sandwiched between two graphite blocks, and then placed in an electric constant temperature blast drying oven for drying. Then it was placed in a tubular furnace in a high-purity Ar atmosphere, and calcined from room temperature to 1300°C at a heating rate of 1°C / min for 8 hours, and then cooled to room temperature at a cooling rate of 1°C / min to obtain a three-dimensional carbon fiber network current collector.
[0039] (2) Preparation of three-dimensional MnO2 cathode by hydrothermal method
[0040] First, add 30mL of deionized water to the 50mL polytetrafluoroethylene liner of the hydrothermal reactor, put in a magnetic stirrer, place the polytetrafluoroethylene liner on a heat-collecting constant temperature heating magnetic stirrer, and stir at a constant temperature. Then, add 0.1g of sodium dodecylbenzene sulfonate to the liner and stir for 10 minutes to fully dissolve it. Add 0.06g of potassium permanganate and stir for 20 minutes to fully dissolve it, then remove the stirrer to obtain a reaction solution. Next, use a polytetrafluoroethylene clamp to fix the three-dimensional carbon fiber network current collector, and then place the clamp in the resulting reaction solution. Then place the polytetrafluoroethylene liner into the hydrothermal reactor, and after installation, place it in an electric constant temperature blast drying oven for hydrothermal reaction at 160°C for 12 hours. After the hydrothermal reactor has naturally cooled to room temperature, take out the clamp, wash it three times with deionized water, and then dry it. Then take out the positive electrode of the in-situ grown MnO2 nanowires on the three-dimensional carbon fiber network on the clamp. Attachment Figure 1 This is the XRD diffraction pattern of the in-situ grown MnO2 nanowire positive electrode of the three-dimensional carbon fiber network current collector. The reference curve is the standard characteristic peak of β-MnO2 (the standard card is JCPDS no.24-0735). The diffraction peaks of the (110), (101), (200), (111), (211), (220), and (301) crystal planes are consistent with the standard spectrum of β-MnO2. The diffraction peak at 2θ=26.5° corresponds to the graphite peak generated by the three-dimensional carbon fiber network current collector under the induction of graphite sheets (marked with *). Attachment Figure 2 This is a scanning electron microscope image of a MnO2 nanowire electrode grown in situ on a three-dimensional carbon fiber network current collector. The MnO2 nanowires are interspersed and grown in the three-dimensional carbon fiber network current collector.
[0041] Finally, the three-dimensional carbon fiber network in situ grown MnO2 nanowire positive electrode was placed in a crucible and calcined at 350°C in a muffle furnace for 12 hours with a heating and cooling rate of 1°C / min. After calcination, a well-crystallized three-dimensional structured MnO2 nanowire positive electrode was obtained.
[0042] (3) Preparation of three-dimensional zinc anode by electroplating
[0043] Using a CHI760C electrochemical workstation, 2M ZnSO4 solution was used as the electrolyte, a three-dimensional carbon fiber network current collector was used as the working electrode, commercial zinc sheets were selected for both the counter electrode and the reference electrode, the deposition potential was selected as -0.8 V, and a three-dimensional zinc negative electrode (galvanized three-dimensional carbon fiber network current collector) was obtained by electroplating for 15 minutes using a constant potential deposition method.
[0044] (4) Preparation of zinc ion batteries with symmetrical three-dimensional positive and negative electrodes
[0045] 11.5g ZnSO4·7H2O and 0.354g MnSO4·H2O were added to 20mL deionized water and stirred for 30min to obtain a mixed solution of 2M ZnSO4 and 0.1M MnSO4 as the electrolyte; the three-dimensional structured MnO2 positive electrode was placed in the central area of the battery shell, and then the glass fiber diaphragm was placed on the positive electrode, and an appropriate amount of electrolyte was dripped until the diaphragm was completely wetted by the electrolyte; then the three-dimensional structured zinc negative electrode was placed in the central area of the wetted diaphragm, and then a stainless steel gasket was placed. After covering the battery negative electrode shell, the button battery was sealed with a button battery packaging machine at a pressure of about 50MPa.
[0046] (5) The electrochemical performance of the zinc ion battery with symmetrical three-dimensional positive and negative electrodes prepared in this example was characterized. Figure 3 This is the charge and discharge cycle performance curve under the conditions of current density of 50mA / g and voltage window of 0.8~1.8V. After 350 charge and discharge cycles, the discharge capacity of the battery is still stable at 300mAh·g -1 .
[0047] Example 2 A method for preparing an aqueous zinc ion battery with a symmetrical three-dimensional positive and negative electrode
[0048] The method for preparing an aqueous zinc ion battery with a symmetrical three-dimensional positive and negative structure in this embodiment comprises the following steps:
[0049] (1) High-temperature preparation of three-dimensional carbon fiber network current collector
[0050] The specific preparation method is the same as that in Example 1.
[0051] (2) Preparation of three-dimensional MnO2 cathode by hydrothermal method
[0052] 2g of sodium dodecylbenzene sulfonate, 0.1g of potassium permanganate and 20mL of deionized water were respectively placed in a polytetrafluoroethylene reactor, and magnetically stirred at room temperature for 50 minutes. The three-dimensional carbon fiber network current collector prepared in step (1) was fixed on a fixture and placed in the reactor. The reaction temperature was 100°C, and the solvent thermal reaction was carried out for 15 hours. After the reaction, it was washed with deionized water, and then dried to obtain a three-dimensional positive electrode of MnO2 nanowires grown on a three-dimensional carbon fiber network. Finally, it was placed in a crucible and calcined at 250°C in a muffle furnace for 15 hours, with a heating and cooling rate of 0.5°C / min. After calcination, a well-crystalline three-dimensional structured MnO2 positive electrode was obtained.
[0053] (3) Preparation of three-dimensional zinc anode by electroplating
[0054] Using a CHI760C electrochemical workstation, 1M ZnSO4 solution was used as the electrolyte, a three-dimensional carbon fiber network current collector was used as the working electrode, commercial zinc sheets were used as the counter electrode and the reference electrode, the deposition potential was selected as -0.5V, and a three-dimensional zinc negative electrode was obtained by electroplating for 5 minutes using constant potential deposition.
[0055] (4) Preparation of zinc ion batteries with symmetrical three-dimensional positive and negative electrodes
[0056] The specific preparation method is the same as that in Example 1.
[0057] Example 3 A method for preparing an aqueous zinc ion battery with symmetrical three-dimensional positive and negative electrodes
[0058] The method for preparing an aqueous zinc ion battery with a symmetrical three-dimensional positive and negative structure in this embodiment comprises the following steps:
[0059] (1) High-temperature preparation of three-dimensional carbon fiber network current collector
[0060] The duck eggshell membrane was immersed in a mixed solution of 40% acetic acid and 80% deionized water for 12 hours. The separated eggshell membrane was washed with anhydrous ethanol and deionized water several times, and then flattened and sandwiched between two alumina blocks, and then placed in an electric constant temperature blast drying oven for drying. Then it was placed in a tubular furnace and calcined at 1400℃ in a high-purity nitrogen atmosphere for 6 hours, with the heating and cooling rates set to 0.5℃ / min, and then cooled to room temperature at a cooling rate of 0.5℃ / min to obtain a three-dimensional carbon fiber network current collector.
[0061] (2) Preparation of three-dimensional MnO2 cathode by hydrothermal method
[0062] 0.05g of sodium dodecylbenzene sulfonate, 0.01g of potassium permanganate and 10mL of deionized water were respectively placed in a polytetrafluoroethylene reactor, and magnetically stirred at room temperature for 20 minutes. The three-dimensional carbon fiber network current collector prepared in step (1) was fixed on a fixture and placed in the reactor. The reaction temperature was 230°C, and the solvent thermal reaction was carried out for 5 hours. After the reaction, it was washed with deionized water, and then dried to obtain a three-dimensional positive electrode of MnO2 nanowires grown on a three-dimensional carbon fiber network. Finally, it was placed in a crucible and calcined at 300°C in a muffle furnace for 5 hours, with a heating and cooling rate of 2°C / min. After calcination, a well-crystalline three-dimensional structured MnO2 positive electrode was obtained.
[0063] (3) Preparation of three-dimensional zinc anode by electroplating
[0064] Using a CHI760C electrochemical workstation, 1M ZnSO4 solution was used as the electrolyte, a three-dimensional carbon fiber network current collector was used as the working electrode, commercial zinc sheets were used as the counter electrode and the reference electrode, the deposition potential was selected as -1.0 V, and a three-dimensional zinc negative electrode was obtained by electroplating for 30 minutes using constant potential deposition.
[0065] (4) Preparation of zinc ion batteries with symmetrical three-dimensional positive and negative electrodes
[0066] The specific preparation method is the same as that in Example 1.
[0067] Comparative Example 1 A method for preparing an aqueous zinc ion battery with an asymmetric electrode structure
[0068] The method for preparing an aqueous zinc ion battery with an asymmetric positive and negative electrode structure in this embodiment comprises the following steps:
[0069] (1) High-temperature preparation of three-dimensional carbon fiber network current collector
[0070] The specific preparation method is the same as that in Example 1.
[0071] (2) Preparation of three-dimensional MnO2 cathode by hydrothermal method
[0072] The specific preparation method is the same as that in Example 1.
[0073] (3) Commercial zinc sheet was directly used as the negative electrode as a comparative example.
[0074] (4) Asymmetric electrode structure zinc ion battery with three-dimensional MnO2 positive electrode and planar zinc sheet negative electrode
[0075] Except that the negative electrode directly uses zinc sheet, the rest of the preparation method is the same as Example 1.
[0076] (5) The electrochemical performance of the asymmetric electrode structure zinc ion battery prepared in this comparative example, which has a three-dimensional structure positive electrode and a planar structure zinc sheet negative electrode, is characterized. Figure 4 This is the charge and discharge cycle performance curve under the conditions of current density of 50mA / g and voltage window of 0.8~1.8V. The initial discharge capacity is 79mAh·g -1 Before the 38th cycle, the capacity increased rapidly to 222 mAh g -1 Then, as the cycle progresses, it rapidly decays to 67 mAh g -1 . This shows that the asymmetric electrode structure of the zinc ion battery has unequal electrochemical reaction rates between the three-dimensional positive electrode and the planar zinc negative electrode. The slower electrochemical reaction rate of the negative electrode makes the initial capacity of the battery lower. As the reaction proceeds, the zinc sheet gradually grows dendrites under the action of the positive and negative electrode electric fields, causing the exposed surface area and electrochemical reaction rate of the negative electrode to gradually increase, which is manifested as a gradual increase in the discharge capacity of the battery. However, when the zinc dendrites increase to a certain length, the zinc dendrites break and fall off to become dead dendrites, or pierce the diaphragm, causing a micro short circuit between the positive and negative electrodes. After that, the discharge capacity gradually decreases with the increase in the number of cycles.
[0077] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.
Claims
1. A method for preparing an aqueous zinc ion battery having a symmetrical three-dimensional positive and negative electrode structure, characterized in that: The following steps are involved: S1, separating the eggshell membrane from the eggshell with an acid solution, drying it, and then heat-treating it under high temperature atmosphere to obtain a three-dimensional carbon fiber network current collector; S2, firstly prepare a reaction solution with sodium dodecylbenzene sulfonate, potassium permanganate and water, then place the three-dimensional carbon fiber network current collector of step S1 in the reaction solution, in situ grow MnO2 nanowires on the three-dimensional carbon fiber network current collector after hydrothermal reaction, and then obtain well-crystallized three-dimensional MnO2 nanowires after calcination; S3, using the three-dimensional carbon fiber network current collector of step S1 as a working electrode, and metal as a counter electrode and a reference electrode, and depositing for a period of time in a constant potential deposition manner to obtain a zinc-plated three-dimensional carbon fiber network current collector; S4, using the three-dimensional MnO2 nanowires of step S2 as the positive electrode and the galvanized three-dimensional carbon fiber network current collector of step S3 as the negative electrode, forming a sandwich structure with the diaphragm and injecting a zinc salt-containing electrolyte, and packaging according to shell-type or soft-pack battery technology to obtain a zinc ion battery with symmetrical three-dimensional positive and negative electrodes.
2. The method for preparing an aqueous zinc ion battery having a positive and negative electrode with a symmetrical three-dimensional structure according to claim 1, wherein: The acid solution in step S1 includes 20% acetic acid solution.
3. The method for preparing an aqueous zinc ion battery having a positive and negative electrode with a symmetrical three-dimensional structure according to claim 1, wherein: The heat treatment temperature in step S1 is 1200-1400° C., the time is 6-10 hours, and the protective atmosphere used is argon or nitrogen.
4. The method for preparing an aqueous zinc ion battery having a positive and negative electrode with a symmetrical three-dimensional structure according to claim 1, wherein: The mass volume ratio of sodium dodecylbenzene sulfonate, potassium permanganate and water in step S2 is 0.05-2 g: 0.01-0.1 g: 10-30 mL.
5. The method for preparing an aqueous zinc ion battery having a positive and negative electrode with a symmetrical three-dimensional structure according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step S2 is 100 to 230° C. and the time is 5 to 15 hours.
6. The method for preparing an aqueous zinc ion battery having a symmetrical three-dimensional positive and negative structure according to claim 1, characterized in that: The calcination temperature in step S2 is 250-350° C. and the calcination time is 5-15 hours.
7. The method for preparing an aqueous zinc ion battery having a symmetrical three-dimensional positive and negative structure according to claim 1, characterized in that: Step S3 is to use zinc metal as the counter electrode and the reference electrode, and use a solution containing 0.5-2M zinc salt as the electrolyte.
8. The method for preparing an aqueous zinc ion battery having a symmetrical three-dimensional positive and negative structure according to claim 1, characterized in that: The constant potential deposition in step S3 has a potential of -1.0 to -0.5 V and a duration of 5 to 30 minutes.
9. The method for preparing an aqueous zinc ion battery having a positive and negative electrode with a symmetrical three-dimensional structure according to claim 1, characterized in that: The hydrothermal reaction in step S2 is carried out in a closed high-temperature and high-pressure reactor, wherein the high-temperature and high-pressure reactor has a metal shell, and a heat-resistant and corrosion-resistant polytetrafluoroethylene lining is provided in the metal shell.
10. An aqueous zinc ion battery having positive and negative electrodes with symmetrical three-dimensional structures, prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Three-dimensional titanium structure and three-dimensional flexible zinc negative electrode with long service life as well as preparation methods and application of three-dimensional titanium structure and three-dimensional flexible zinc negative electrode
CN113046795A
Preparation method of nano three-dimensional conductive framework / MnO2 composite structure material and application of the nano three-dimensional conductive framework / MnO2 composite structure material in zinc battery positive electrode
CN110364693A
Zinc negative electrode with zinc ion conductivity interface modification layer, battery and preparation method
CN111933912A